Vitamin D Deficiency and Oral Mucositis in Hematopoietic Stem Cell Transplantation: A Cross-Sectional Observation - Kosar Raoufinejad; Shahrzad Pezeshki; Bahram Chahardouli; Molouk Hadjibabaie; Zahra Jahangard-Rafsanjani; Kheirollah Gholami; Mehdi Rajabi; Mohammad Vaezi (Research Center for Rational Use of Drugs (RCRUD), 2019)
Backgrounds: One of the most frequent complications of high-dose chemotherapy regimen before hematopoietic stem cell transplantation (HSCT) is oral mucositis (OM). Vitamin D (VD) has well-known immunoregulatory, anti-inflammatory, and antioxidant properties. Objectives: This study aimed to evaluate the association of baseline VD levels with OM as well as neutrophil and platelet engraftments in patients with multiple myeloma, Hodgkin's and non-Hodgkin's lymphoma after autologous HSCT. Methods: A sample of 71 patients was included after obtaining informed consent. Serum samples were collected in the morning prior to the administration of conditioning regimen to measure the baseline 25-OH-D. OM was examined daily during hospital stay. The WHO scale was used for scoring the OM. Absolute neutrophil count and platelet count were determined daily from transplantation until engraftment. Results: Patients aged between 18 to 65 years. Mean length of hospital stay was 15.8±5.7 days. OM was detected in 44/71 (62.0%) of patients. Mean time to the engraftment of neutrophils and platelets were 11.8±4.0 and 17.2±7.3 days, respectively. Mean level of baseline 25-OH-D was 17.5±14.0 ng/ml. VD deficiency (<20 ng/ml) was diagnosed in 51/71 (71.8%) of patients. No association between baseline 25-OH-D levels and the incidence of OM (P=0.69) or OM grade 3-4 (P=0.46) was found. No significant correlations were detected between the baseline 25-OH-D and engraftment time of neutrophils (P=0.46) or platelets (P=0.17). Conclusions: The prevalence of VD deficiency was high among adult HSCT patients at the time of transplantation. No association was found between low baseline VD with post-HSCT OM and engraftment time.